Concept of Reverse Micelle Method For the Synthesis of Nano-Structured Materials - Lone, Irfan H.; Radwan, Nagi R.E.; Aslam, Jeenat; Akhter, Arifa (Current Nanoscience, 2019)
Synthesis of nanomaterials with desired shape and size is very important for their potential applications. The properties of the nanoparticles synthesis not only vary with size but also changes with shape and morphology which in turn depends on the synthesis methods. There are many synthesis methods but among them reverse micellar method is one of the interesting chemical method and is very useful technique for the synthesis of nanoparticles with desired shape and size. In this method revere micelles are formed by least three components; two of them are non-miscible and the third one is called surfactant which is characterized by amphiphilic properties.
Keywords: hydoplillic